UKF-Based Parameter Estimation and Identification for Permanent Magnet Synchronous Motor - Wang, Zhiwei; Liu, Xin; Wang, Wenzhuo; Lv, Yunling; Yuan, Bo; Li, Wujing; Li, Qiufang; Wang, Shijie; Chen, Qianchang; Zhang, Yi (Frontiers in Energy Research, 2022)
The accuracy of rotor position estimation determines the performance of the sensorless control system of a permanent magnet synchronous motor. In order to realize the accurate control of rotor position and speed, it is necessary to identify the motor parameters. Modeling and simulation of the state estimation are investigated for a permanent magnet synchronous motor with parameter identification based on the unscented Kalman filter (UKF) in this article. Based on the mathematical model of the motor, the unscented Kalman filter is used to identify the rotor flux and quadrature axis inductance simultaneously, and the identified parameters are used to update the motor model in the sensorless vector control algorithm. The simulation results show that the unscented Kalman filter can converge to the real value in a short time with small errors. It can follow the changes of motor parameters well and achieve high-precision speed and position estimation.